Affordable Excellence - William A. Haseltine (Brookings Institution Press, 2013)
is book was inspired by a speech given in 2010 by then Minister for Health of Singapore, Khaw Boon Wan, to an international group of health specialists. I had the good fortune to attend the meeting of NIHA (the Initiative to Improve Health in Asia), a Pan-Asian Policy Program sponsored by the National University of Singapore and the Global Asia Institute. e Minister’s speech outlined the history and more importantly, the thinking, behind the creation of the Singapore healthcare system. e system he described is both effective and unique. I asked if a book existed describing the Singapore approach to healthcare and was surprised to learn that none did. A few weeks later, I had a follow-up conversation over dinner with the NUS President, Tan Chorh Chuan, Director of the Global Asia Institute, Seetharam Kallidaikurichi Easwaran, and Paul Kratoska, then Director of NUS Press who encouraged me to write this volume. Seetharam Kallidaikurichi kindly provided support for a researcher for a year and the book was on its way. I mentioned that I was writing a volume on the Singapore healthcare system that might provide lessons in the creation of sustainable healthcare system to others in both developing and developed countries to Strobe Talbott of the Brookings Institution, and he and his colleagues kindly offered to jointly publish the book with NUS Press. I am grateful to Robert Faherty, Director of the Brookings Press for his encouragement. I thank Peter Schoppert, now Director of NUS Press, for his enthusiasm and assistance.